WRITING PROFICIENCY IN TRANSPARENT ORTHOGRAPHIES: WHEN DO ROMANIAN CHILDREN START TO SPELL CORRECTLY? - DACIAN DORIN DOLEAN; DANIEL ANDRONACHE (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. Spelling abilities of elementary and middle school students can vary across languages. One major variable that influences students' spelling performance is the degree of orthographic regularity of their native language. In our study, we measured the writing performance of four hundred and forty four Romanian students attending 2nd, 3rd, 4th, 6th and 8th grade of the same school. Results indicated that overall, there were no significant differences in spelling performance of students after 3rd grade. They also suggest that learning the phoneme‐grapheme correspondence of regular words reaches ceiling within the 1st year of instruction (97% proficiency). Limitations of this study are being addressed.